Estimation of Phytochemicals from Mother Plants and In vitro Raised Plants of Gloriosa superba - Sharma, Sneh; Devi, Bandna; Sharma, Vivek (International Journal of Economic Plants, 2021)
Gloriosa superba L. is an important endangered medicinal plant and widely used in Indian system of medicine. All the parts of Gloriosa superba keeps several biological activities such as antioxidant, antimicrobial, antibacterial and anthelmintic properties. This is due to the presence of different phytochemicals like alakloids, flavonoids, phenols, tannins, glycosides, saponins, carbohydrates, steroids and minerals in tubers, leaves and stem. Methanol extract of leaves of mother plant showed higher phenolic content (93.80±0.22 mg GAE g-1) and flavanoids (11.47±0.26 mg QE g-1) than in in vitro raised plants. Acetone extract of stem of mother plant showed highest concentration of tannins (70.83±0.88 mg TAE g-1).